Living Through a Pandemic with Birds - Kim, Bo Sun (Journal of Childhood Studies, 2023)
The COVID-19 pandemic highlights the intricate interdependence among humans and other living creatures. It is imperative for educators to acknowledge these connections and embrace an approach that recognizes humans as part of the shared world, woven together with other species and elements. To commit to such an approach, educators should reckon with their pedagogical dispositions and orientations toward the world and incorporate them into their teaching. The curriculum inquiry “Living with Birds” offers a renewed perspective by examining the everyday interactions and relationships among children, educators, a pedagogist, and birds, and their ethical and pedagogical implications in an early childhood context.